Preservice Teachers’ Perceptions of Linguistic Abilities and Privacy Policies in the Use of Visual Materials During Their Own and Their Tutors’ Lessons - Míguez-Álvarez, Carla; Cuevas-Alonso, Miguel; Doval-Ruiz, María Isabel (Frontiers in Education, 2022)
This article analyzes the capacity for improvement of digital observation in initial teacher training to investigate whether the implementation of visual materials is effective for the reinforcement of previously taught content, the assessment of one’s own linguistic abilities and whether it motivates learners. To do so, the subjects analyzed classroom behavior and learning typology through the reflection of their own videos recorded with children and tutors. Data was collected through 12 closed-ended questions that follow the Likert scale and one open-ended question for general reflection. The questions focused on the motivation and interest of the students with respect to the videos viewed, comprehension, learning, perceived usefulness and the problem arising with the privacy of the students' personal data. The responses were classified and their frequencies and percentages were calculated. The results show that implementing video tools in the classroom and reflecting on their content afterwards can be an effective means of assessing one's learning and language skills. In addition, the study highlights the inherent complexities posed by EU GDPR regulations and the significant barriers to integrating video technology into the classroom for schoolchildren in these contexts.